Ibalong new central Bicol station - Sarmiento, Kate P. (College of Architecture, University of the Philippines Diliman, 2019)
Transport as a support facility directly connects north and south, connects places and people. Transport facilities are also the first destination point upon arriving in a particular place. This is an immense potential to introduce the place or the community in that place. However, most transport facilities, particularly here in the Philippines, usually have utilitarian design with little or no cultural translation in the spaces. In this thesis, the design aims to emphasize translation of culture in spaces. It uses technology to translate efficiency of spaces without losing identity of place instead using identity as the main feature of the design. The outcome of the thesis shoes that the design of utilitarian spaces, particularly that of transport facility, does not need to detach itself from its community, the people, and the culture of the place it is located in to be able to be efficient and effective in doing its purpose.